Rethinking gene regulatory networks in light of alternative splicing, intrinsically disordered protein domains, and post-translational modifications - Niklas, Karl J.; Bondos, Sarah E.; Dunker, A. Keith; Newman, Stuart A. (Frontiers in Cell and Developmental Biology, 2015)
Models for genetic regulation and cell fate specification characteristically assume that gene regulatory networks (GRNs) are essentially deterministic and exhibit multiple stable states specifying alternate, but pre-figured cell fates. Mounting evidence shows, however, that most eukaryotic precursor RNAs undergo alternative splicing (AS) and that the majority of transcription factors contain intrinsically disordered protein (IDP) domains whose functionalities are context dependent as well as being subject to post-translational modification (PTM). Consequently, many transcription factors do not have fixed cis-acting regulatory targets, and developmental determination by GRNs alone is untenable. These phenomena require multi-scale models for how GRNs operationally interact with the intra- and intercellular environments. Evidence shows that these features, which complicate gene expression, can act synergistically, to facilitate and promote time- and cell-specific protein modifications involved in cell signaling and cell fate specification while disrupting a strict deterministic GRN-phenotype mapping. The combined effects of AS, IDP, and PTM give proteomes physiological plasticity, adaptive responsiveness, and developmental versatility without inefficiently expanding genome size. It also helps us understand how protein functionalities can undergo major evolutionary changes via AS, IDP, and PTM buffering of mutational consequences.